Proposição de uma escala para mensuração de responsabilidade social corporativa no varejo brasileiro - Garcia, Eduardo (2013)
Considering the fact that the first tracts that mention Corporate Social Responsibility (CSR) exist for more than hundred years, this topic is not a new one. Since the sixties, more profound treats have appeared and moreover, several concepts have been developed and discussed. Till the end of the seventies there was no concordance about how to standardize the conceptualization of CSR. In 1979, Archie Carroll developed an approach in which he tried to synthesize and schematize those concepts. He compiled them in four quadrants named after the factors economy, legality, ethics and confidentiality. According to this definition, all existing concepts could be placed within these four quadrants. Although the importance of CSR was already well-known there was no means of measurement of this construct that consumers would understand. Within this gap, the principal intention of this work is to propose and evaluate a scale that enables consumers to measure CSR. By the means of a survey that included 862 end-consumers of chain stores, the relation between the multidimensional composition of CSR was tested and by valuation of the name, the effect of this loyalty (r2 = 0.58) and satisfaction (r2 = 0.70) was proved. As a result of this investigation, a valid and reliable scale was developed. It contains 9 items of rating which were set up in the tridimensional ambient of CSR that was acknowledged by the treats of Schwartz and Carroll (2003) who considered economy, legality and ethics as the forming factors.